Hanging ball training on top serve ability in extracurricular volleyball - Togar Sari, Wahyu; Destriana, Destriana; Aryanti, Silvi (Physical Education Departement of University PGRI Jombang, 2024)
This study aims to determine the effect of hanging ball training on top serve ability in volleyball extracurricular activities for female students of North Indralaya 1 Public Senior High School. The method used in this research was a quasi-experiment with a pretest-posttest one group design. The sampling technique is total population sampling with a sample size of 30 people. The treatment in this study was hanging ball training given for 6 weeks with a training frequency of 3 times a week. The results of data processing and analysis using the data normality test and hypothesis testing with the t test formula show that hanging ball training has an effect on the results of the top serve. This can be seen from the results of data analysis through calculating the t test formula with the criterion tcount being greater than ttable (19.28 > 1.70) with a significance level of α = 0.05 and the number of samples (N = 30), then the hypothesis proposed accepted. Hanging ball training has an influence on the results of top serve ability. The research results showed that hanging ball training hanging ball training is useful for teachers and coaches as a guide to improving the top serve in volleyball extracurricular activities for female students of North Indralaya 1 Public Senior High School.